2011
DOI: 10.1136/bmjqs-2011-000173
|View full text |Cite
|
Sign up to set email alerts
|

Lean thinking transformation of the unsedated upper gastrointestinal endoscopy pathway improves efficiency and is associated with high levels of patient satisfaction

Abstract: Lean thinking transformation of the unsedated UGI endoscopy pathway results in reduced waiting times, reduced staffing requirements and improved patient flow and can form the basis of a pathway template which may be successfully transferred into alternative endoscopy environments with high levels of patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 19 publications
0
20
0
2
Order By: Relevance
“…[17][18][19] However, in a 2015 systematic review of use of lean techniques in health care, researchers reported positive but not conclusive evidence of improved quality and safety outcomes. These inconclusive results may be due in part to a need to delineate what implementation strategies led to the success of QI initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] However, in a 2015 systematic review of use of lean techniques in health care, researchers reported positive but not conclusive evidence of improved quality and safety outcomes. These inconclusive results may be due in part to a need to delineate what implementation strategies led to the success of QI initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…A lean transformation of an out-patient department  phlebotomy service in a teaching affiliate to Harvard Medical School reduced the average patient waiting times from 21 to 5 min, and improved patient satisfaction 16. Similar benefits from lean improvement strategies in the outpatient environment have been demonstrated in the UK and the Netherlands 17 18. There are indeed other benefits, in addition to workflow improvement, from lean thinking service redesign, although these were beyond the scope of this pilot project.…”
Section: Discussionmentioning
confidence: 66%
“…É possível que haja efeitos indiretos nos resultados, pois o VSM é uma ferramenta operacional de aplicação restrita a um processo ou a um serviço específico. No entanto Chiarini (2014) bem como Faulkner e Bardurdeen (2014), relatam efeitos positivos do VSM no meio ambiente enquanto que Hydes et al (2012) e Souza et al (2013) relatam melhor atendimento ao cliente como resultados finais.…”
Section: Saídas E Resultadosunclassified
“…No entanto, existe um significativo número de pesquisas feito no setor de health care (17 casos), onde 5 (cinco) publicações estão relacionadas ao setor privado como Kaale et al (2005), Kocakulah e Upson (2005), Ng et al (2010), Schwarz et al (2011), Wong et al (2012, 10 (dez) publicações ao setor público como Lummus et al (2006), Grove et al (2010), L'Hommedieu e Kappeler (2010), Cima et al (2011), Carter et al (2012), Chiarini, (2012, Hydes et al (2012), Teichgraber e de Bucourt (2012), Chiarini (2013), Abdelhadi e Shakoor (2014) e 2 (duas) publicações, como Cookson et al (2011) e Xie e Peng (2012), o setor econômico não foi mencionado.…”
Section: Contextounclassified